Dificultades en el aprendizaje y recuperación de nombres propios en el envejecimiento - Simón López, Teresa (Revista de Investigación en Logopedia, 2012)
A common complaint of older adults is that they have trouble remembering names, even the names of people they know well. This paper attempts to analyze this problem by reviewing the features of proper names, the theoretical models of production and the results found in aging to finally make a proposal for intervention on difficulties of learning and retrieval of personal names. This proposal is based on the experimental results of the studies reviewed and it highlights the importance of phonological and semantic clues, the need to train other cognitive skills (also highly demanding and often affected by age) that are related to the ability to name persons and includes the possibility of introducing metamnic strategies to facilitate this task. Finally further research in this area is needed to test the effectiveness of some interventions that have been raised but have not been proved yet.